Nascent Entrepreneurs - Joachim Wagner (Institute for the Study of Labor (IZA), 2004)
Nascent entrepreneurs are people who are engaged in creating new ventures. This chapter reviews the international evidence on how many of them are there around the world, what they are doing, who they are, what makes them different, and which ones see their vision through to eventual start-up.
Keywords: J23; 330; nascent entrepreneurs; literature review; Unternehmer; Unternehmensgründung; Welt